COMPARING GC AND FIELD LMXBs IN ELLIPTICAL GALAXIES WITH DEEP CHANDRA AND HUBBLE DATA - Kim, D; Fabbiano, G; Brassington, N; Fragos, T; Kalogera, V; Zezas, A; Jordan, A; Sivakoff, G; Kundu, A; Zepf, SE; Angelini, L; Davies, R; et al. (Institute of Physics Publishing, 2009)
We present a statistical study of the low-mass X-ray binary (LMXB) populations of three nearby, old elliptical galaxies: NGC 3379, NGC 4278, and NGC 4697. With a cumulative 1 Ms Chandra ACIS observing time, we detect 90-170 LMXBs within the D25 ellipse of each galaxy. Cross-correlating Chandra X-ray sources and HST optical sources, we identify 75 globular cluster (GC) LMXBs and 112 field LMXBs with LX > 1036 erg s-1 (detections of these populations are 90% complete down to luminosities in the range of 6 × 1036 to 1.5 × 10 37ergs-1). At the higher luminosities explored in previous studies, the statistics of this sample are consistent with the properties of GC-LMXBs reported in the literature. In the low-luminosity range allowed by our deeper data (LX < 5 × 1037 erg s-1), we find a significant relative lack of GC-LMXBs, when compared with field sources. Using the co-added sample from the three galaxies, we find that the incompleteness-corrected X-ray luminosity functions (XLFs) of GC and field LMXBs differ at 4σ significance at LX < 5 × 1037 erg s-1. As previously reported, these XLFs are consistent at higher luminosities. The presently available theoretical models for LMXB formation and evolution in clusters are not sophisticated enough to provide a definite explanation for the shape of the observed GC-LMXB XLF. Our observations may indicate a potential predominance of GC-LMXBs with donors evolved beyond the main sequence, when compared to current models, but their efficient formation requires relatively high initial binary fractions in clusters. The field LMXB XLF can be fitted with either a single power-law model plus a localized excess at a luminosity of (5-6) × 1037 erg s-1, or a broken power law with a similar low-luminosity break. This XLF may be explained with NS-red-giant LMXBs, contributing to 15% of total LMXBs population at 5 × 1037 erg s-1. The difference in the GC and field XLFs is consistent with different origins and/or evolutionary paths between the two LMXB populations, although a fraction of the field sources are likely to have originated in GCs. © 2009 The American Astronomical Society. All rights reserved.